Patterns and Implications of Intracranial Arterial Remodeling in Stroke Patients - Qiao, Ye (Stroke, 2016)
BACKGROUND AND PURPOSE: Preliminary studies suggest ntracranial arteries are capable of accommodating plaque formation by remodeling. We sought to study the ability and extent of intracranial arteries to remodel using 3D high-resolution black blood MRI (BBMRI) and investigate its relation to ischemic events. METHODS: 42 patients with cerebrovascular ischemic events underwent 3D time-of-flight MRA and contrast-enhanced BBMRI examinations at 3T for intracranial atherosclerotic disease. Each plaque was classified by location (e.g., posterior vs. anterior circulation) and its likelihood to have caused a stroke identified on MRI (culprit, indeterminate, or non-culprit). Lumen area (LA), outer wall area (OWA), and wall area (WA) were measured at the lesion and reference sites. Plaque burden was calculated as WA divided by OWA. The arterial remodeling ratio (RR) was calculated as OWA at the lesion site divided by OWA at the reference site, after adjusting for vessel tapering. Arterial remodeling was categorized as positive if RR >1.05, intermediate if 0.95≤RR ≤ 1.05, and negative if RR <0.95. RESULTS: 137 plaques were identified in 42 patients (37% [50] posterior, 63% [87] anterior). Compared with anterior circulation plaques, posterior circulation plaques had a larger plaque burden (77.7±15.7 vs. 69.0±14.0, p=0.008), higher RR (1.14±0.38 vs. 0.95±0.32, p=0.002), and more often exhibited positive remodeling (54.0% vs.29.9%, p=0.011). Positive remodeling was marginally associated with downstream stroke presence when adjusted for plaque burden (OR 1.34, 95% CI: 0.99–1.81). CONCLUSIONS: Intracranial arteries remodel in response to plaque formation, and posterior circulation arteries have a greater capacity for positive remodeling and, consequently, may more likely elude angiographic detection. Arterial remodeling may provide insight into stroke risk.